The Health-Benefits and Phytochemical Profile of Salvia apiana and Salvia farinacea var. Victoria Blue Decoctions - Andrea F. Afonso; Olívia R. Pereira; Ângela S. F. Fernandes; Ricardo C. Calhelha; Artur M. S. Silva; Isabel C.F.R. Ferreira; Susana M. Cardoso (MDPI AG, 2019)
Salvia apiana and Salvia farinacea var. Victoria Blue decoctions were screened for diverse bioactivities, including the ability to counteract oxidative and inflammatory events, as well as to act as cytotoxic and antimicrobial agents. Both extracts showed good activities and that of S. apiana origin was particularly effective regarding the ability to prevent lipid peroxidation and to prevent nitric oxide (NO●) production in lipopolysaccharide (LPS)-activated murine macrophage RAW 264.7 cell line (EC50 = 50 μg/mL). Moreover, it displayed high cytotoxic capacity against hepatocellular carcinoma HepG2, cervical carcinoma HeLa, and breast carcinoma cells MCF-7, but comparatively low effects in porcine liver primary cells, which highlights its selectivity (GI50 = 41−60 μg/mL vs. 362 μg/mL, respectively). Further, it exhibited inhibitory and lethal potential against a panel of Gram-positive and Gram-negative bacteria. It is possible that the bioactive properties of the two Salvia extracts are associated to their phenolic components and, in the particular case of S. apiana, to its richness in phenolic terpenes, namely in rosmanol, hydroxycarnosic acid and a derivative of sageone, which were found in the extract.